General Subject Didactics. Development - theoretical insights - empirical results - Vollmer, Helmut Johannes; Rothgangel, Martin (Journal of curriculum studies, 2025)
The article deals with a new scientific approach developed under the title of 'General Subject Didactics'. This concept is based on the existence of several academic disciplines called 'subject didactics' or 'subject(−matter) didactics'. These are linked to certain scientific domains like biology or mathematics and to respective school subjects. The goal was to observe and reflect on how the individual subject didactics explore subject-specific teaching and learning, both by top-down reflections and by bottom-up comparisons. In terms of design, 17 subject didactics within Germany were compared and analyzed on the basis of six impulses. This empirical study allowed us to gain basic insights into the commonalities of all related subject-didactic disciplines and to identify differences among them. In this way, General Subject Didactics was developed step by step in a comparative way. As a result it can be defined as a theory of subject didactics. This innovative approach feeds into an extended content- or knowledge-based philosophy of education.